2020
DOI: 10.3390/cancers13010101
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CDK5 in Tumours and Tumour Microenvironments

Abstract: Cyclin-dependent kinase 5 (CDK5), which belongs to the protein kinase family, regulates neuronal function but is also associated with cancer development and has been proposed as a target for cancer treatment. Indeed, CDK5 has roles in cell proliferation, apoptosis, angiogenesis, inflammation, and immune response. Aberrant CDK5 activation triggers tumour progression in numerous types of cancer. In this review, we summarise the role of CDK5 in cancer and neurons and CDK5 inhibitors. We expect that our review hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 244 publications
(182 reference statements)
0
20
0
Order By: Relevance
“…low CDK3 expression and high CDK5 and CDK8 expression are associated with poor survival. CDK3 has been reported to promote myoblast cell proliferation; 31 Yue et al showed that CDK5 promotes the proliferation of medullary thyroid carcinoma cells; 32 in addition, Chen et al showed that the promotion of OSCC cell proliferation by direct binding of miR-567 leads to increased CDK8 expression. 33 These previous findings suggest that CDK3, CDK5 and CDK8 is an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…low CDK3 expression and high CDK5 and CDK8 expression are associated with poor survival. CDK3 has been reported to promote myoblast cell proliferation; 31 Yue et al showed that CDK5 promotes the proliferation of medullary thyroid carcinoma cells; 32 in addition, Chen et al showed that the promotion of OSCC cell proliferation by direct binding of miR-567 leads to increased CDK8 expression. 33 These previous findings suggest that CDK3, CDK5 and CDK8 is an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 5 (CDK5) is a member of the protein kinase family that has been shown to play a role in cancer development and the TME ( Do and Lee, 2020 ). Abnormal activation of CDK5 affects the development of triple negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that TMB score and MSI was positively correlated with the expression of EFNA3 and EFNA4 in gastric cancer. Cyclin-dependent kinase 5 (CDK5) is a member of the protein kinase family that has been shown to play a role in cancer development and the TME (Do and Lee, 2020). Abnormal activation of CDK5 affects the development of triple negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, there could be additional reasons for the failure of roscovitine to improve GC-induced impaired bone healing. For example, because Cdk5 is known to regulate inflammation [ 91 , 92 , 93 , 94 ], its inhibition could possibly exacerbate GC effects on the immune response upon fracture, which is essential for downstream regenerative processes [ 22 , 88 , 89 , 95 ]. Another possible reason could be that Cdk5 inhibition or high-dose GCs adversely affects angiogenesis [ 16 , 96 , 97 , 98 , 99 , 100 , 101 ], a process that is essential for uneventful fracture healing [ 89 , 95 ].…”
Section: Discussionmentioning
confidence: 99%